Pengaruh Era Digital terhadap Kompetensi Berbahasa Indonesia Generasi Z (Pusat riset dan Inovasi Nasional, 2026)
The progress of the era accompanying the growth of Generation Z has made it easier and faster for Generation Z to socialize. In this digital era, people are likely to use Indonesian that does not conform to the rules. Sometimes, code-mixing occurs among Generation Z. This study was conducted to determine whether the digital era really has a significant influence on the language competence of Generation Z. This study, which uses a quantitative descriptive method, is expected to be one of many studies discussing the language skills of Generation Z. To that end, this study distributed questionnaires to 108 people from Generation Z. The results show that the level of influence of the digital era is moderate, while the language competence of the respondents is quite good, with an average score of 28.04. These findings indicate that even though Generation Z actively uses digital media and is often exposed to non-standard language on social media, their Indonesian language skills are still fairly well maintained. Therefore, the digital era does not significantly reduce language competence, although good language awareness is still necessary to prevent the quality of Indonesian from falling.